A Model Suggestion for the Recovery of Women Exposed to Violence: Tidal Model - Mahire Olcay Cam; Emel Ozturk Turgut (Psikiyatride Güncel Yaklaşımlar, 2019)
Violence against women is an important healthcare problem. Noncontrollable increasing in violence and, healthcare politics that focus on rehabilitation services lay emphasis on fighting outcomes of violence. Although violent behaviors are similar, each woman's experience is unique so healthcare services must be individualized. Tidal Model is a recovery model in healthcare services that cares individualism. For this reason in this review the suitability of the tidal model was assessed in line with the question “Can violent women be given nursing care based on Tidal Model?”. Partner or domestic violence against to women was examined.